EVALUASI PEMBELAJARAN DARING TERHADAP MATERI PEMBELAJARAN IPA KELAS IX SMPN 18 KOTA BENGKULU - Anggi Prasani; Desti Herdiyanti; Lisa Puspita; Ahmad Walid (Academy of Education Journal, 2021)
This study aims to determine the quality of students through online methods during the pandemic in science subjects at SMPN 18 Bengkulu City. The method used in this research is to use qualitative methods. The data analysis technique used is a qualitative descriptive technique. The results showed that the science learning material at SMPN 18 Bengkulu City was in the above average category with a total of 27 students who scored between 80-85 and as many as 5 students who scored between 86-90.